Yuvak mandals : a study on the working of select mandals in five states - Jain, S. P., 1940- (National Institute of Rural Development, 1978)
With reference to youth organizations in Andhra Pradesh, Karnataka, Rajasthan, Uttar Pradesh, and West Bangal.